Mycoplasma hyopneumoniae Infection Activates the NOD1 Signaling Pathway to Modulate Inflammation - Liu, Wei; Jiang, Pengcheng; Yang, Keli; Song, Qiqi; Yuan, Fangyan; Liu, Zewen; Gao, Ting; Zhou, Danna; Guo, Rui; Li, Chang; Sun, Pei; Tian, Yongxiang (Frontiers in Cellular and Infection Microbiology, 2022)
Mycoplasma hyopneumoniae is a highly contagious pathogen causing porcine enzootic pneumonia, which elicits prolonged inflammatory response modulated by pattern recognition receptors (PRRs). Although significant advances have been achieved in understanding the Toll-Like receptors that recognize M. hyopneumoniae, the role of nucleotide-binding oligomerization domain 1 (NOD1) in M. hyopneumoniae infected cells remains poorly understood. This study revealed that M. hyopneumoniae activates the NOD1-RIP2 pathway and is co-localized with host NOD1 during infection. siRNA knockdown of NOD1 significantly impaired the TRIF and MYD88 pathway and blocked the activation of TNF-α. In contrast, NOD1 overexpression significantly suppressed M. hyopneumoniae proliferation. Furthermore, we for the first time investigated the interaction between M. hyopneumoniae mhp390 and NOD1 receptor, and the results suggested that mhp390 and NOD1 are possibly involved in the recognition of M. hyopneumoniae. These findings may improve our understanding of the interaction between PRRs and M. hyopneumoniae and the function of NOD1 in host defense against M. hyopneumoniae infection.